EVALUATION OF MONOBORE DRILLING WELL ARCHITECTURE IN PT PERTAMINA HULU INDONESIA ZONA 9 PARTICULARLY IN STRUCTURE-X - Winardi Tammala, Alvine
In the context of the high-risk, high-investment oil and gas industry, operational efficiency plays a pivotal role in profitability, making Key Performance Indicators (KPI) a crucial focal point. In 2021, the oil production downturn in PEP TSS, particularly in the drilling sector, raised concerns about the financial outlook. The condition became tamed after merging with PHSS which created an opportunity to knowledge transfer from one another. This actually prompts a critical examination of the potential for implementing monobore well architecture, notably in StructureX. Monobore design, renowned for its cost-effective approach to wellbore design, production, and completion, emerges as a promising avenue for financial recovery for PEP TSS. The research stages encompass a thorough literature review, analysis of primary and secondary data, quantitative assessments. Assumptions revolve around the cost-effectiveness and performance improvements achievable through monobore, supported by the hypothesis that it can outperform conventional well architecture with high chance of success findings indicating a mere 14% probability of NPV < 0 and an estimated $0.54 million USD increase in profitability compared to conventional well architecture, suggesting significant potential for financial gains in the industry.